Causes and post-divorce experiences among initiators and non-initiators - Annie Margaret, Sandela Raran (2023)
Terminating a marriage is an experience where couples move from a destructive relationship to divorce. This study was aimed to discover the divorce factors, divorce experiences, and counselling perceptions of initiators and non-initiators under the contested proceedings of (LRA, 1976). A qualitative phenomenological approach was adapted in this study. Semi-structured, in-depth phenomenological interviews, and legal file analysis were conducted with 14 participants. Thematic analyses were used to demonstrate analytical rigour in the stages of coding and the identification of emergent themes through the use of Nvivo. Realiability and validity were accomplished through audio recording, triangulation, and bracketing. The findings of the divorce factors revealed five core themes: marital incompatibility, family factors, infidelity and extramarital affairs, starting a new life, and financial problems. Results of divorce experiences indentified six core themes that were related to negative self-belief, blaming spouses, mental torture, confirmed and decisive decisions about divorce, long-term tolerance, and abandonment and rejection. Results of counselling perception identified five core themes that were related to long counselling procedures, schedulling, counselor credibility, counselor perceptions, and tribunal’s process/procedures. Findings indicate, on average, participants who opened a file with the Legal Aid Department in Perak under contested proceedings had their marriage irretrievably broken down. Therefore, the findings underwrite the fact that it is just and fair to have a "decent burial" in divorce as these relationships are unquestionably dead. Simultaneously, the study's findings show that counseling, which was used as a partial substitute for divorce failed to achieve its goal of reconciling the couples.